2022
DOI: 10.1007/s10479-022-04813-1
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Evaluating sustainably resilient supply chains: a stochastic double frontier analytic model considering Netzero

Abstract: In era of reglobalization, sustainably resilient supply chains (SCs) are imperative in corporations to improve performance and meet stockholders’ expectations. However, sustainably resilient SCs could not be effective if are not assessed by using advanced frameworks, systems, and models. As such, developing a novel network data envelopment model (DEA) to appraise sustainably resilient SCs is our purpose in this article. To do so, we present a new double-frontier methodology to provide optimistic and pessimisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 106 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…While each of these research concepts has been studied individually or in a coupled (pairwise) form (Chopra et al, 2021;Hosseini, et al, 2020;Lücker et al, 2021;Cadden et al, 2022;, we need to look beyond the traditional technology infrastructure and focus on organizational structure and dynamics (leadership, culture, skills and competencies) to unpack antecedents for effective AI integration within organisations (such as SMEs) that will help to drive green, lean and agile decision-making for achieving SC resilience. While the importance of SC resilience, CE practices and AI-enabled digital transformation has been increasingly recognized by the research community (Baryannis, et al, 2019;Naz et al, 20212021b;Azadi et al, 2022;Wicaksana et al, 2022;Iftikhar et al, 2022: Ganesh et al, 2022, integrating these concepts to provide empirical insights is critical to making supply chain management practices sustainable, operationally productive, and resilient, while simultaneously responding to the UN sustainability development goals, the challenges posed by the pandemic, and operating in line with the governmental regulations and strategies. Zouari et al, 2021 have showed the positive influence of AI adoption on SC resilience (in a direct one-one relationship), however the position of our research is that AI adoption will facilitate operationalising and strategizing CE practices, SC risk management and SC agility through data-driven decision-making, which will lead to SC resilience.…”
Section: Knowledge Gaps and Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…While each of these research concepts has been studied individually or in a coupled (pairwise) form (Chopra et al, 2021;Hosseini, et al, 2020;Lücker et al, 2021;Cadden et al, 2022;, we need to look beyond the traditional technology infrastructure and focus on organizational structure and dynamics (leadership, culture, skills and competencies) to unpack antecedents for effective AI integration within organisations (such as SMEs) that will help to drive green, lean and agile decision-making for achieving SC resilience. While the importance of SC resilience, CE practices and AI-enabled digital transformation has been increasingly recognized by the research community (Baryannis, et al, 2019;Naz et al, 20212021b;Azadi et al, 2022;Wicaksana et al, 2022;Iftikhar et al, 2022: Ganesh et al, 2022, integrating these concepts to provide empirical insights is critical to making supply chain management practices sustainable, operationally productive, and resilient, while simultaneously responding to the UN sustainability development goals, the challenges posed by the pandemic, and operating in line with the governmental regulations and strategies. Zouari et al, 2021 have showed the positive influence of AI adoption on SC resilience (in a direct one-one relationship), however the position of our research is that AI adoption will facilitate operationalising and strategizing CE practices, SC risk management and SC agility through data-driven decision-making, which will lead to SC resilience.…”
Section: Knowledge Gaps and Research Questionsmentioning
confidence: 99%
“…recognized by the research community (Baryannis, et al, 2019;Naz et al, 20212021b;Azadi et al, 2022;Wicaksana et al, 2022;Iftikhar et al, 2022: Ganesh et al, 2022, integrating these concepts to provide empirical insights is critical to making supply chain management practices sustainable, operationally productive, and resilient, while simultaneously responding to the UN sustainability development goals, the challenges posed by the pandemic, and operating in line with the governmental regulations and strategies. Zouari et al, 2021 have showed the positive influence of AI adoption on SC resilience (in a direct one-one relationship), however the position of our research is that AI adoption will facilitate operationalising and strategizing CE practices, SC risk management and SC agility through data-driven decision-making, which will lead to SC resilience.…”
Section: Knowledge Gaps and Research Questionsmentioning
confidence: 99%
“…It is considered a comprehensive and useful assessment of supply chain risk (Kraude et al, 2022). DEA is commonly used in many areas, including supply chain management (Azadi et al, 2022) and transport (Akbar et al, 2020). When mentioning the applications of the DEA method, it is worth emphasising its particular usefulness for assessing objects and processes that cannot be characterised in financial terms, e.g., the public sector: foundations, education institutions, and, e.g., technology .…”
Section: Transport Risk Assessment Techniquesmentioning
confidence: 99%